Effect of adjuvant/neoadjuvant trastuzumab on clinical outcomes in patients with HER2‐positive metastatic breast cancer. Issue 13 (26th March 2014) - Murthy, Rashmi K.; Varma, Ankur; Mishra, Priyankana; Hess, Kenneth R.; Young, Elliana; Murray, James L.; Koenig, Kimberly H.; Moulder, Stacy L.; Melhem‐Bertrandt, Amal; Giordano, Sharon H.; Booser, Daniel; Valero, Vicente; et al.
Abstract : BACKGROUND: The purpose of the current study was to describe the outcomes of patients with human epidermal growth factor receptor 2 (HER2)‐overexpressed/amplified (HER2+) early breast cancer who received adjuvant or neoadjuvant trastuzumab‐based therapy and were subsequently retreated with trastuzumab for metastatic disease. METHODS: A total of 353 patients with metastatic HER2+ breast cancer who were treated with trastuzumab as part of their first‐line treatment for metastatic disease were identified. A total of 75 patients had received adjuvant or neoadjuvant trastuzumab‐based therapy for early breast cancer, and 278 had not. Clinical outcomes of patients who had or had not received prior trastuzumab were compared using Cox proportional hazards regression and logistic regression analyses. Survival was estimated using the Kaplan‐Meier method. RESULTS: The clinical benefit (complete response, partial response, or stable disease of ≥ 6 months) rates were 71% in the group who did not receive prior trastuzumab and 39% in the group previously treated with trastuzumab. The adjusted odds ratios were 0.28 (95% confidence interval [95% CI], 0.13‐0.59; P = .0009) for clinical benefit rates and 0.39 (95% CI, 0.18‐0.82; P = .038) for objective (complete or partial) response rates. In the univariate analysis, the median overall survival rate was longer in the group who did not receive prior trastuzumab (36 months vs 28 months) (hazards ratio, 1.47; 95% CI, 1.07‐2.01 [ P = .022]). The multivariate analysis found no significant difference in overall survival. CONCLUSIONS: When treated with trastuzumab for metastatic disease, patients with HER2+ breast cancer without prior exposure to trastuzumab were found to have superior clinical outcomes to those with prior exposure. Prior trastuzumab exposure should be considered in treatment algorithms and in HER2‐targeted clinical trial enrollment for metastatic disease. Cancer 2014;120:1932–1938 . © 2014 American Cancer Society . Abstract : Trastuzumab‐naive patients with human epidermal growth factor receptor 2 (HER2)‐positive metastatic breast cancer have superior clinical outcomes to those patients treated with trastuzumab‐based therapy. Prior trastuzumab exposure should be considered in the design of clinical trials and sequencing of HER2‐targeted therapies.